Masjid Al Mahmudiyah Dan Penyebaran Islam Di Wilayah Suro Palembang Tahun 1920-1925 Masehi - Rakha Agusti Amanullah; Hudaidah (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
In the city of Palembang there is a mosque named “Al-Mahmudiyah Mosque”, which was originally known as Suro Mosque. This mosque is one of the real proofs of the strategic role as the propagation of Islam. This mosque is not only a spiritual symbol, but also a driving force of Islamic da‘wah that was very influential, especially in the Suro area in the early 20th century. The purpose of writing this study is motivated by the unique position of the mosque which rose from the period of colonial oppression, which is a religious activities were prohibited for more than three decades, and then became a symbol of spiritual and social revival of the local Muslim community. This research uses the historical method with a qualitative approach, through the tracing of archives, colonial documents, as well as interviews with community leaders and descendants of local ulama. The results of the study reveal that after the lifting of the colonial prohibition, Al-Mahmudiyah Mosque carried out multidimensional roles. Religiously, the construction of the minaret (1925) and the revitalization of Friday prayers and Islamic study circles functioned as effective tools of consolidation and education of the ummah. Thus, Al-Mahmudiyah Mosque can be regarded as a center of da‘wah and strengthening of Islamic identity that also shaped the religious dynamics of the Suro community of Palembang in the early 20th century AD.